Análisis del impacto de las redes sociales sobre el tráfico web de los cibermedios nativos digitales españoles - Dr. David PARRA VALCARCE,Lda. Charo ONIEVA MALLERO (Fonseca, Journal of Communication, 2023)
The commitment of digital native cybermedia for social networks as strategic instruments to increase the volume of web traffic to their portals is based on aspects such as the consolidation of the manual semantic web or the emergence of prosumers. The main purpose of this article is to analyze to what extent it is true that these platforms contribute to in-creasing the number of visitors and whether or not the effort made by the information industry in order to be part of them is justified.